2017
DOI: 10.1371/journal.pone.0188498
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency cabin air filter in vehicles reduces drivers' roadway particulate matter exposures and associated lipid peroxidation

Abstract: Commuters who spend long hours on roads are exposed to high levels of traffic related air pollutants (TRAPs). Despite some well-known multiple adverse effects of TRAPs on human health, limited studies have focused on mitigation strategies to reduce these effects. In this study, we measured fine particulate matter (PM2.5) and ultrafine particle (UFP) concentrations inside and outside 17 taxis simultaneously while they were driven on roadways. The drivers’ urinary monohydroxylated polycyclic aromatic hydrocarbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 49 publications
0
23
0
3
Order By: Relevance
“…In comparison with other studies, UFP levels recorded inside Lebanese taxis were 1.6-fold higher than those measured in Los Angeles. 20 Nevertheless, they were considerably much lower than in-taxis UFP concentrations reported in two distinct studies conducted in London 18,27 and in Barcelona. 28 These differences may be explained first by the variation in the time/duration of measurement.…”
Section: Ufp Levels Inside Taxi Vehiclesmentioning
confidence: 74%
See 3 more Smart Citations
“…In comparison with other studies, UFP levels recorded inside Lebanese taxis were 1.6-fold higher than those measured in Los Angeles. 20 Nevertheless, they were considerably much lower than in-taxis UFP concentrations reported in two distinct studies conducted in London 18,27 and in Barcelona. 28 These differences may be explained first by the variation in the time/duration of measurement.…”
Section: Ufp Levels Inside Taxi Vehiclesmentioning
confidence: 74%
“…WC + AC + ARM offered between 47% and 90% of UFP protection inside cabs. 20,30,40 Furthermore, Onat et al 41 found that UFP levels were 80% higher in vehicles when WO and they were more than doubled in Moreno et al 28 and in Los Angeles (mean: 19 ± 20 μg m −3 ) cars 46 and slightly higher than in Singapore taxis (GM: 2.9 μg m −3 ). 47 Such divergence may be the result of both windows opening/closing status and engine types.…”
Section: Influence Of Ventilation Settingsmentioning
confidence: 97%
See 2 more Smart Citations
“…Human resources are equally important for ongoing maintenance of monitors, such as general checks, replacing parts, changing filters, recalibration, etc. [12]. Finally, extracted data needs to be ratified through a lengthy curation process, enabling data to be ready for public dissemination and communication.…”
Section: Monitoring Realities -Setting Up An Air Quality Monitoring Nmentioning
confidence: 99%